Highly branched pentasaccharide-bearing amphiphiles for membrane protein studies - Ehsan,M; Du,Y; Scull,NJ; Tikhonova,E; Tarrasch,J; Mortensen,JS; Loland,CJ; Skiniotis,G; Guan,L; Byrne,B; Kobilka,BK; Chae,PS (Journal of the American Chemical Society, 2016)
Detergents are essential tools for membrane protein manipulation. Micelles formed by detergent molecules have the ability to encapsulate the hydrophobic domains of membrane proteins. The resulting protein–detergent complexes (PDCs) are compatible with the polar environments of aqueous media, making structural and functional analysis feasible. Although a number of novel agents have been developed to overcome the limitations of conventional detergents, most have traditional head groups such as glucoside or maltoside. In this study, we introduce a class of amphiphiles, the PSA/Es with a novel highly branched pentasaccharide hydrophilic group. The PSA/Es conferred markedly increased stability to a diverse range of membrane proteins compared to conventional detergents, indicating a positive role for the new hydrophilic group in maintaining the native protein integrity. In addition, PDCs formed by PSA/Es were smaller and more suitable for electron microscopic analysis than those formed by DDM, indicating that the new agents have significant potential for the structure–function studies of membrane proteins.